Assessment of the roles of reactive oxygen species in the UV and visible light photocatalytic degradation of cyanotoxins and water taste and odor compounds using C–TiO2. (1st March 2016) - Fotiou, Theodora; Triantis, Theodoros M.; Kaloudis, Triantafyllos; O'Shea, Kevin E.; Dionysiou, Dionysios D.; Hiskia, Anastasia
Abstract: Visible light (VIS) photocatalysis has large potential as a sustainable water treatment process, however the reaction pathways and degradation processes of organic pollutants are not yet clearly defined. The presence of cyanobacteria cause water quality problems since several genera can produce potent cyanotoxins, harmful to human health. In addition, cyanobacteria produce taste and odor compounds, which pose serious aesthetic problems in drinking water. Although photocatalytic degradation of cyanotoxins and taste and odor compounds have been reported under UV-A light in the presence of TiO2, limited studies have been reported on their degradation pathways by VIS photocatalysis of these problematic compounds. The main objectives of this work were to study the VIS photocatalytic degradation process, define the reactive oxygen species (ROS) involved and elucidate the reaction mechanisms. We report carbon doped TiO2 (C–TiO2 ) under VIS leads to the slow degradation of cyanotoxins, microcystin-LR (MC-LR) and cylindrospermopsin (CYN), while taste and odor compounds, geosmin and 2-methylisoborneol, were not appreciably degraded. Further studies were carried-out employing several specific radical scavengers (potassium bromide, isopropyl alcohol, sodium azide, superoxide dismutase and catalase) and probes (coumarin) to assess the role of different ROS (hydroxyl radical OH, singlet oxygen 1 O2, superoxide radical anion O 2 − ) in the degradation processes. Reaction pathways of MC-LR and CYN were defined through identification and monitoring of intermediates using liquid chromatography tandem mass spectrometry (LC-MS/MS) for VIS in comparison with UV-A photocatalytic treatment. The effects of scavengers and probes on the degradation process under VIS, as well as the differences in product distributions under VIS and UV-A, suggested that the main species in VIS photocatalysis is O 2 −, with OH and 1 O2 playing minor roles in the degradation. Graphical abstract: Highlights: Degradation and intermediates produced under C–TiO2 /VIS photocatalysis. Definition of ROS role during MC-LR C–TiO2 /VIS photocatalysis using scavengers and probes. O 2 − /HO2 are the main species during photocatalysis under VIS using C–TiO2 HO and 1 O2 play a minor role in the process New intermediate products for MC-LR and CYN under C–TiO2 /VIS.